Serum zinc-alpha(2)-glycoprotein concentrations in patients with non-alcoholic fatty liver disease - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2011)
Background: Evidence suggests that zinc-alpha(2)-glycoprotein (ZAG) might serve as a biomarker for human metabolic alterations. We measured serum ZAG in patients with nonalcoholic fatty liver disease (NAFLD), a hepatic manifestation of the metabolic syndrome, and examined its association with clinical, biochemical, and histological phenotypes. Methods: Serum ZAG was determined using ELISA in 90 patients with biopsy-proven NAFLD and 81 controls. Results: Serum ZAG concentrations did not differ in patients with NAFLD (median 61 mu g/mL; interquartile range: 56-73 mu g/mL) compared with healthy controls (median 66 mu g/mL; interquartile range: 56-78 mu g/mL, Mann-Whitney U-test, p = NS). However, among patients with NAFLD serum ZAG concentrations were significantly higher in males and in those with the metabolic syndrome. After step-wise linear regression analysis, serum ZAG concentrations were the only independent predictor of the number of metabolic syndrome components in patients with NAFLD (beta = 0.22; t = 2.001, p<0.05). Conclusions: In summary, the hypothesis of an association between NAFLD and serum ZAG concentrations is not supported by the present results. However, ZAG remains an interesting molecule for further research in the field of human metabolic disorders.
Keywords: enzyme-linked immunosorbent assay; non-alcoholic fatty liver disease; zinc-alpha(2)-glycoprotein; METABOLIC SYNDROME